Preference and views on lecture delivery methods of clinical students in Bayero University Medical School - NJBCS, Author (Nigerian Journal of Basic and Clinical Sciences, 2026)
Background:Lectures are essential parts of undergraduate medical education for the transfer of information to students. The traditional method of lecture delivery is widely practiced while some lecturers prefer the use of multimedia powerpoint.Objectives:This study intends to find out the preference and views on lecture delivery methods among the clinical students of Bayero University Medical School.Materials and Methods:This is a descriptive cross-sectional study involving the 400, 500 and 600 levels students. Self-administered pretested questionnaires were administered. Data were analysed by the use of frequencies and percentages. The difference between the various classes was analysed using one-way ANOVA with aP< 0.05 considered to be significant.Results:The age range is between 20 and 41 years with a mean age of 24.9 ± 2.91. There are 171 males and 90 females with a male: female ratio of 1.9:1. The predominant method of lecture delivery by teachers is the use of multimedia powerpoint, 215 (82.4%). Most of the students, 185 (70.9%) prefer a combination of the traditional and powerpoint methods, whereas 13 (12.6%) prefer the use of powerpoint while a minority 33 (5%), the traditional method. Majority, 181 (69.3%) are of the view that the duration of lectures should not exceed 1 h.Conclusion:A combination of the traditional method and multimedia powerpoint is the preferred lecture delivery method of Bayero University clinical students and they opined that lectures should not exceed an hour.